Élite sport & employability: Theoretical frameworks, policies and educational perspectives - Sergio Bellantonio; Domenico Tafuri (Firenze University Press, 2019)
Increasing emphasis on the importance of adult education programs in European agenda has led to a focus on the employability of élite athletes too. In the field of sport studies, there has been little research into the relationship between élite sport and employability. This paper wants to reflect on the nature of sports and training paths today from an educational perspective and the possible implications for the development of best practices within this context of life and experience. A new approach on sport and education is necessary, based both on learning outcomes and evidence-based strategies which will lead to the best possible match between the needs of society and requirements of the job market, even in sport.   Sport d'élite ed employability: presupposti teorici, orientamenti politici e prospettive educative L'interesse crescente per l'importanza dei programmi di educazione degli adulti nell'agenda europea ha richiesto anche un'attenzione specifica all'employability degli atleti d'élite. All'interno degli sport studies ci sono ancora poche ricerche sulla relazione che viene a stabilirsi tra lo sport di alto livello e l'employability, per tal motivo, lo scopo di questo articolo è quello di riflettere sulla natura dei percorsi sportivi e di formazione oggi, attraverso un punto di vista educativo che sia a sostegno di possibili implicazioni per lo sviluppo di buone pratiche all'interno di tale contesto di vita e d'esperienza. È necessario un nuovo approccio allo sport e all'educazione, basato sia sui risultati dell'apprendimento sia su strategie d'intervento basate sull'evidenza, le quali possono condurre alla miglior articolazione possibile tra bisogni della società e richieste del mercato del lavoro, anche in ambito sportivo.